Miss Pettigrew lives for a day - Watson, Winifred, 1906-2002 (Persephone, 2008)
Miss Pettigrew, a governess looking for work, is sent by mistake to the home of Delysia LaFosse, a glamorous nightclub singer involved with three different men and is invited to stay after offering Miss LaFosse common sense advice about her love life.